HOSPITALITY INDUSTRY IN MODERN CONDITIONS: RECENT TRENDS AND PROBLEMS OF DEVELOPMENT - I. Rogova (Вестник университета)
Hospitality industry is a rapidly developing industry even in conditions of economic crisis and unstable political situation. In this article the analysis of the world market of the hotel industry, modern tendencies of development in actual conditions of conducting economic activity is resulted. The place of hospitality industry in the world economy system is considered. The analysis of the reasons of high attractiveness and profitability of hotel business is resulted. Innovative trends and main problems of hotel industry development in Russia and in the world are investigated.